2020
DOI: 10.1021/acs.langmuir.9b03208
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of PEO–PPO–PEO Block Copolymer and PEO Homopolymer in Lipid Bilayers

Abstract: Maintaining the integrity of cell membranes is indispensable for cellular viability. Poloxamer 188 (P188), a poly(ethylene oxide)-b-poly(propylene oxide)-b-poly(ethylene oxide) (PEO−PPO−PEO) triblock copolymer with a numberaverage molecular weight of 8700 g/mol and containing 80% by mass PEO, protects cell membranes from various external injuries and has the potential to be used as a therapeutic agent in diverse applications. The membrane protection mechanism associated with P188 is intimately connected with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 59 publications
(120 reference statements)
4
26
0
Order By: Relevance
“…PEO chains when functionalized with hydrophobic molecules, such as pairs of dodecyl or cholesteryl ends, can anchor to the outer hydrophilic part of the bilayer, while chains form a “mushroom” or “brush” conformation that changes the rigidity of the bilayer . Extending to longer blocks such as PEO–PPO (poly­(propylene oxide)) diblock copolymers or PEO–PPO–PEO triblock copolymers, also known as poloxamers, introduce the opportunity to manipulate the liposomes from inside the bilayer and from the aqueous phase. ,, Poly­(oxyethylene alkyl ethers) (C i E j ) or n -alkyl PEO polymers are at an intermediate position between PEO and diblock copolymers such as PEO–PPO. These n -alkyl PEO polymers consisting of hydrophilic poly­(ethylene oxide) chains connected to simple hydrophobic alkyl chains are nonionic surfactant-like polymers that can show multiple self-assembled structures. These are commonly used in soaps and detergents in combination with other surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…PEO chains when functionalized with hydrophobic molecules, such as pairs of dodecyl or cholesteryl ends, can anchor to the outer hydrophilic part of the bilayer, while chains form a “mushroom” or “brush” conformation that changes the rigidity of the bilayer . Extending to longer blocks such as PEO–PPO (poly­(propylene oxide)) diblock copolymers or PEO–PPO–PEO triblock copolymers, also known as poloxamers, introduce the opportunity to manipulate the liposomes from inside the bilayer and from the aqueous phase. ,, Poly­(oxyethylene alkyl ethers) (C i E j ) or n -alkyl PEO polymers are at an intermediate position between PEO and diblock copolymers such as PEO–PPO. These n -alkyl PEO polymers consisting of hydrophilic poly­(ethylene oxide) chains connected to simple hydrophobic alkyl chains are nonionic surfactant-like polymers that can show multiple self-assembled structures. These are commonly used in soaps and detergents in combination with other surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Poloxamers are a specific class of linear block polymer amphiphile of poly­(ethylene oxide) (PEO) and poly­(propylene oxide) (PPO) segments that are commercially available (e.g., Pluronics), are biocompatible, and have demonstrated efficacy as cell membrane stabilizing agents against many types of stresses. , A range of prior studies have focused on the mechanisms of poloxamer–lipid interactions; however, a complete picture of the stabilization mechanism is still lacking. ,, , Amphiphilic bottlebrush polymers have potential as a tool to yield additional mechanistic insights, through architectural variation. Bottlebrush polymers have multiple parameters to tune (e.g., backbone length, graft length, graft spacing), and aspects of the relationships among these parameters and molecular properties, such as segmental dynamics, molecular shape, and ability to share space, are understood.…”
mentioning
confidence: 99%
“…However, PBO units could facilitate a deeper insertion depth for the polymer compared to PPO, but further studies are needed to confirm this. It should be noted that Kim, et al found that at high polymer concentration (≈40 mg/mL) P188 and PEO similarly permeated bilayers composed of POPC . Therefore, the PEO block could also play a part in facilitating membrane association.…”
Section: Results and Discussionmentioning
confidence: 96%